Dietary advanced glycation end products (AGEs) and type 2 diabetes (T2D): a case-control study - Salman Alharbi, Saud; M. Mirza, Iman; Ibrahim Alzahrani, Wala; O. Alsulami, Seham; Hamdan Alsaqri, Salman; Alanazi, Sultan Mohammed; Shehab, Gaber Mohamed Gomaa (Frontiers in Nutrition, 2026)
BackgroundAdvanced glycation end products (AGEs), which are formed through non-enzymatic reactions between sugars and proteins or lipids, are abundant in diets high in processed foods and those cooked at high temperatures. Growing evidence suggests that dietary AGEs may contribute to oxidative stress, inflammation, and insulin resistance, thereby influencing the development of type 2 diabetes (T2D). This study aimed to investigate the association between dietary AGE intake and the risk of developing T2D in adults.MethodsThis case-control study included 225 adults recently diagnosed with type 2 diabetes and 450 healthy controls (18–60 years) recruited from Tabuk University Hospital. Dietary advanced glycation end product (AGE) intake was estimated using a proprietary scoring method based on the AGE content (kU/100 g) of 108 food items listed in a validated food frequency questionnaire (FFQ). Logistic regression models, adjusted for potential confounders, were applied to calculate odds ratios (ORs) and 95% confidence intervals (CIs) for type 2 diabetes across tertiles of dietary AGE intake.ResultsAmong 675 participants (53% male; mean age = 38.13 ± 8.85 years; mean BMI = 26.85 ± 4.31 kg/m2), individuals with T2D had significantly higher median dietary AGE intake scores than controls (4,186 vs. 2,798 kU/100 g, P < 0.001). In fully adjusted logistic regression models, higher dietary AGE intake remained independently associated with increased odds of T2D. Compared with the lowest tertile, the highest tertile of AGE intake showed an adjusted odds ratio (OR) = 2.16 (95% CI: 1.06–4.09; P for trend < 0.001). In sensitivity analyses that included additional adjustment for key dietary components and modeled AGEs as a log-transformed continuous variable, each one–standard deviation increase in Ln(AGEs) was associated with a 42% higher odds of T2D (OR = 1.42; 95% CI: 1.04–1.95; P = 0.015). Stratified analyses indicated that this association was stronger and statistically significant primarily among individuals with overweight or obesity (BMI ≥25 kg/m2).ConclusionThe findings indicate that higher dietary intake of AGEs is strongly associated with increased odds of type 2 diabetes, independent of major confounders. These results support growing evidence that diets rich in processed and high-heat–cooked foods contribute to metabolic disturbances and highlight the potential benefits of reducing AGE intake as part of diabetes prevention strategies. Further prospective and interventional studies are needed to confirm these findings and clarify the causal mechanisms involved.